Using phonetics to teach children between the ages 10 to 12 of the "Centro Infantil y Guarderia La Florida" to read in french at a basic level (level A1, according to the common european framework of reference for languages), year 2016 - Henríquez Varela, Yasmin Ivette; Rodríguez, Yeimi Lisset; Villegas Guardado, Daniel Isaías (2024)
The present project is an investigation related to the use of Phonetics as a method to teach children of “Centro Infantil y Guarderia La Florida” San Salvador, to read in French to help them achieve the A1 level according to the Common European Framework of Reference for Languages. Phonetics is the branch of Linguistics that studies the articulate language in human speech (Bertil Malmberg “La Fonética”, 1977). In the opinion of linguists such as James Gibson, Phillip Gregory, and many others, this discipline is strongly connected to the ability of children to learn to read, if it is applied with the correct techniques and methods